OPTIMALISASI PERTUMBUHAN ANAK DAN PENGENTASAN STUNTING MELALUI INOVASI “MAS DANU SIAB CETING” DI KELURAHAN DANUKUSUMAN, KECAMATAN SERENGAN, KOTA SURAKARTA - Pramono, Ahmad; Aji, Aditia Pemana; Salsabila, Malida; Paramesti, Widyadary; Ad’nin, Atika Rishalah; Shonata, Mutiara; Pranasita, Christella Quinta; Putra, Muhammad Ilham Rizky; Shiyami, Tsalatsatun Nisa’ Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to examine efforts to optimize child growth and reduce stunting through Mas Danu Siab Ceting's innovation in Danukusuman Village, Serengan District, Surakarta City. The research method used is qualitative with a case study approach. Data was collected through participant observation, in-depth interviews, and analysis of documents related to innovation programs. The research results show that Mas Danu Siab Ceting's innovation has succeeded in gathering active participation from the community and various related parties in efforts to improve the quality of children's nutrition and reduce stunting rates. Through integrated programs, such as nutritional education, providing additional food, and regular monitoring of children's growth, there has been a significant improvement in children's nutritional status and a reduction in stunting rates in Danukusuman Village. These findings show that Mas Danu Siab Ceting's innovation has great potential in overcoming the problem of stunting at the local level. This research makes an important contribution to understanding effective strategies for optimizing child growth and alleviating stunting through community-based innovation